System analysis of metabolism and the transcriptome in Arabidopsis thaliana roots reveals differential co‐regulation upon iron, sulfur and potassium deficiency. (28th November 2016) - Forieri, Ilaria; Sticht, Carsten; Reichelt, Michael; Gretz, Norbert; Hawkesford, Malcolm J.; Malagoli, Mario; Wirtz, Markus; Hell, Ruediger
Abstract: Deprivation of mineral nutrients causes significant retardation of plant growth. This retardation is associated with nutrient‐specific and general stress‐induced transcriptional responses. In this study, we adjusted the external supply of iron, potassium and sulfur to cause the same retardation of shoot growth. Nevertheless, limitation by individual nutrients resulted in specific morphological adaptations and distinct shifts within the root metabolite fingerprint. The metabolic shifts affected key metabolites of primary metabolism and the stress‐related phytohormones, jasmonic, salicylic and abscisic acid. These phytohormone signatures contributed to specific nutrient deficiency‐induced transcriptional regulation. Limitation by the micronutrient iron caused the strongest regulation and affected 18% of the root transcriptome. Only 130 genes were regulated by all nutrients. Specific co‐regulation between the iron and sulfur metabolic routes upon iron or sulfur deficiency was observed. Interestingly, iron deficiency caused regulation of a different set of genes of the sulfur assimilation pathway compared with sulfur deficiency itself, which demonstrates the presence of specific signal‐transduction systems for the cross‐regulation of the pathways. Combined iron and sulfur starvation experiments demonstrated that a requirement for a specific nutrient can overrule this cross‐regulation. The comparative metabolomics and transcriptomics approach used dissected general stress from nutrient‐specific regulation in roots of Arabidopsis. Abstract : Acquisition of mineral nutrients by plants is of crucial importance for growth and ultimately yield of crops. In recent years, the presence of a general nutrient‐deficiency‐induced transcriptional response has been hypothesized on the basis of global transcriptome analyses from plants starved for diverse nutrients. By comparative investigation of iron, sulfur and potassium deficiency, we provide evidence that only a small number of genes was regulated in a sense of a general nutrient‐deficiency response. However, we observed nutrient‐specific phenotypic adaptations and specific alterations of the root phytohormone system in response to individual nutrient deficiencies. A comprehensive analysis of sulfur and iron assimilation‐related metabolites revealed individual patterns in response to the diverse nutrient deficiencies. Dissection of the transcriptome responses to the three nutrients showed cross‐talk between the metabolism of iron and sulfur. The lack of such cross‐talk under potassium deficiency underpinned the specificity of this interaction. Detailed analysis of this cross‐talk revealed that the iron and sulfur uptake and metabolization pathways were oppositely regulated upon starvation by these nutrients.